Health system barriers influencing timely breast cancer diagnosis and treatment among women in low and middle-income Asian countries: evidence from a mixed-methods systematic review - Agani Afaya; Sheena Ramazanu; Obasanjo Afolabi Bolarinwa; Vida Nyagre Yakong; Richard Adongo Afaya; Richard Gyan Aboagye; Silas Selorm Daniels-Donkor; Ahmed-Rufai Yahaya; Jinhee Shin; Veronica Millicent Dzomeku; Martin Amogre Ayanore; Robert Kaba Alhassan (BMC, 2022)
Abstract Background Globally, breast cancer is the most common cancer type and the leading cause of cancer mortality among women in developing countries. A high prevalence of late breast cancer diagnosis and treatment has been reported predominantly in Low- and Middle-Income Countries (LMICs), including those in Asia. Thus, this study utilized a mixed-methods systematic review to synthesize the health system barriers influencing timely breast cancer diagnosis and treatment among women in Asian countries. Methods We systematically searched five electronic databases for studies published in English from 2012 to 2022 on health system barriers that influence timely breast cancer diagnosis and treatment among women in Asian countries. The review was conducted per the methodology for systematic reviews and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, while health system barriers were extracted and classified based on the World Health Organization (WHO)'s Health Systems Framework. The mixed-methods appraisal tool was used to assess the methodological quality of the included studies. Results Twenty-six studies were included in this review. Fifteen studies were quantitative, nine studies were qualitative, and two studies used a mixed-methods approach. These studies were conducted across ten countries in Asia. This review identified health systems barriers that influence timely breast cancer diagnosis and treatment. The factors were categorized under the following: (1) delivery of health services (2) health workforce (3) financing for health (4) health information system and (5) essential medicines and technology. Delivery of health care (low quality of health care) was the most occurring barrier followed by the health workforce (unavailability of physicians), whilst health information systems were identified as the least barrier. Conclusion This study concluded that health system factors such as geographical accessibility to treatment, misdiagnosis, and long waiting times at health facilities were major barriers to early breast cancer diagnosis and treatment among Asian women in LMICs. Eliminating these barriers will require deliberate health system strengthening, such as improving training for the health workforce and establishing more healthcare facilities.